ANALISIS EFEKTIFITAS PENERAPAN BALANCED SCORECARD PADA PT SURVEYOR INDONESIA - , Roby Barmawanto; , Dr. Eko Suwardi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objectives of the study are to analyze the effectiveness of the implementation of Balanced Scorecard ("BSC") in the PT Surveyor Indonesia ("PT SI"), i.e. by comparing the underlying theory and available research results to the practice of BSC in the PT SI. According to PT SI, BSC is an important management tool because the BSC has been used as a strategic planning and control tools, as well as performance measurement tools. The effectiveness of the implementation of BSC is measured in terms of achievement of the managementâs objectives by implementing BSC, the number of benefits obtained, as well as the suitability of the practice of BSC in the company with the principles adopted by successful companies who were implementing BSC. The study was conducted by learning how the practice of implementation of BSC in the company, which was obtained from written documents obtained as well as interviews with the management. Interviews were intended to confirm the understanding of the authors upon the practice took place in the company. Furthermore, the authors assessed the achievement of the managementâs objectives. The author also compared the benefits generally obtained by companies that had implemented the BSC with the benefits already obtained the management of PT SI. In the next section, the authors also assessed the fit between the principles applied by the strategy-focused organization with practices in the Company. The analysis result could be used especially by the management of PT SI in considering further improvement of the BSC in their environment. Finally, this thesis concluded that the PT SI has been quite effective implemented BSC, in terms of gaining benefit from the application of the BSC as well as the successfully implementation some basic principles of strategy-focused organization. However, the management of the Company still has the potential to gain greater benefit if they can improve further the pattern of BSC implementation.